Presentation is loading. Please wait.

Presentation is loading. Please wait.

6.3 – Evaluating Polynomials. degree (of a monomial) 5x 2 y 3 degree =

Similar presentations


Presentation on theme: "6.3 – Evaluating Polynomials. degree (of a monomial) 5x 2 y 3 degree ="— Presentation transcript:

1 6.3 – Evaluating Polynomials

2 degree (of a monomial) 5x 2 y 3 degree =

3 degree (of a monomial) 5x 2 y 3 degree =

4 degree (of a monomial) 5x 2 y 3 degree = 5

5 degree (of a monomial) 5x 2 y 3 degree = 5 degree

6 degree (of a monomial) 5x 2 y 3 degree = 5 degree (of a polynomial w/1 variable)

7 degree (of a monomial) 5x 2 y 3 degree = 5 degree (of a polynomial w/1 variable) - highest exponent of a single term

8 degree (of a monomial) 5x 2 y 3 degree = 5 degree (of a polynomial w/1 variable) - highest exponent of a single term Ex. 1 State the degree and leading coefficient of the polynomial. 7x 4 + 5x 2 + x – 9

9 degree (of a monomial) 5x 2 y 3 degree = 5 degree (of a polynomial w/1 variable) - highest exponent of a single term Ex. 1 State the degree and leading coefficient of the polynomial. 7x 4 + 5x 2 + x – 9 degree =

10 degree (of a monomial) 5x 2 y 3 degree = 5 degree (of a polynomial w/1 variable) - highest exponent of a single term Ex. 1 State the degree and leading coefficient of the polynomial. 7x 4 + 5x 2 + x – 9 degree =

11 degree (of a monomial) 5x 2 y 3 degree = 5 degree (of a polynomial w/1 variable) - highest exponent of a single term Ex. 1 State the degree and leading coefficient of the polynomial. 7x 4 + 5x 2 + x – 9 degree =

12 degree (of a monomial) 5x 2 y 3 degree = 5 degree (of a polynomial w/1 variable) - highest exponent of a single term Ex. 1 State the degree and leading coefficient of the polynomial. 7x 4 + 5x 2 + x 1 – 9 degree =

13 degree (of a monomial) 5x 2 y 3 degree = 5 degree (of a polynomial w/1 variable) - highest exponent of a single term Ex. 1 State the degree and leading coefficient of the polynomial. 7x 4 + 5x 2 + x 1 – 9x 0 degree =

14 degree (of a monomial) 5x 2 y 3 degree = 5 degree (of a polynomial w/1 variable) - highest exponent of a single term Ex. 1 State the degree and leading coefficient of the polynomial. 7x 4 + 5x 2 + x – 9 degree = 4

15 degree (of a monomial) 5x 2 y 3 degree = 5 degree (of a polynomial w/1 variable) - highest exponent of a single term Ex. 1 State the degree and leading coefficient of the polynomial. 7x 4 + 5x 2 + x – 9 degree = 4 lead coeff. =

16 degree (of a monomial) 5x 2 y 3 degree = 5 degree (of a polynomial w/1 variable) - highest exponent of a single term Ex. 1 State the degree and leading coefficient of the polynomial. 7x 4 + 5x 2 + x – 9 degree = 4 lead coeff. =

17 degree (of a monomial) 5x 2 y 3 degree = 5 degree (of a polynomial w/1 variable) - highest exponent of a single term Ex. 1 State the degree and leading coefficient of the polynomial. 7x 4 + 5x 2 + x – 9 degree = 4 lead coeff. = 7

18 Funtional Values

19 Ex. 2 Find the following functional values if p(x) = x 3 + 4x 2 – 5x

20 Funtional Values Ex. 2 Find the following functional values if p(x) = x 3 + 4x 2 – 5x a. p(-5)

21 Funtional Values Ex. 2 Find the following functional values if p(x) = x 3 + 4x 2 – 5x a. p(-5)

22 Funtional Values Ex. 2 Find the following functional values if p(x) = x 3 + 4x 2 – 5x a. p(-5) p(-5) =

23 Funtional Values Ex. 2 Find the following functional values if p(x) = x 3 + 4x 2 – 5x a. p(-5) p(-5) =

24 Funtional Values Ex. 2 Find the following functional values if p(x) = x 3 + 4x 2 – 5x a. p(-5) p(-5) = (-5) 3

25 Funtional Values Ex. 2 Find the following functional values if p(x) = x 3 + 4x 2 – 5x a. p(-5) p(-5) = (-5) 3 + 4(-5) 2

26 Funtional Values Ex. 2 Find the following functional values if p(x) = x 3 + 4x 2 – 5x a. p(-5) p(-5) = (-5) 3 + 4(-5) 2 – 5(-5)

27 Funtional Values Ex. 2 Find the following functional values if p(x) = x 3 + 4x 2 – 5x a. p(-5) p(-5) = (-5) 3 + 4(-5) 2 – 5(-5)

28 Funtional Values Ex. 2 Find the following functional values if p(x) = x 3 + 4x 2 – 5x a. p(-5) p(-5) = (-5) 3 + 4(-5) 2 – 5(-5) = -125

29 Funtional Values Ex. 2 Find the following functional values if p(x) = x 3 + 4x 2 – 5x a. p(-5) p(-5) = (-5) 3 + 4(-5) 2 – 5(-5) = -125 + 4(25)

30 Funtional Values Ex. 2 Find the following functional values if p(x) = x 3 + 4x 2 – 5x a. p(-5) p(-5) = (-5) 3 + 4(-5) 2 – 5(-5) = -125 + 4(25) – 5(-5)

31 Funtional Values Ex. 2 Find the following functional values if p(x) = x 3 + 4x 2 – 5x a. p(-5) p(-5) = (-5) 3 + 4(-5) 2 – 5(-5) = -125 + 4(25) – 5(-5) = -125 + 100

32 Funtional Values Ex. 2 Find the following functional values if p(x) = x 3 + 4x 2 – 5x a. p(-5) p(-5) = (-5) 3 + 4(-5) 2 – 5(-5) = -125 + 4(25) – 5(-5) = -125 + 100 + 25

33 Funtional Values Ex. 2 Find the following functional values if p(x) = x 3 + 4x 2 – 5x a. p(-5) p(-5) = (-5) 3 + 4(-5) 2 – 5(-5) = -125 + 4(25) – 5(-5) = -125 + 100 + 25 = -25 + 25

34 Funtional Values Ex. 2 Find the following functional values if p(x) = x 3 + 4x 2 – 5x a. p(-5) p(-5) = (-5) 3 + 4(-5) 2 – 5(-5) = -125 + 4(25) – 5(-5) = -125 + 100 + 25 = -25 + 25 = 0

35 b. p(3a)

36 p(x) = x 3 + 4x 2 – 5x

37 b. p(3a) p(x) = x 3 + 4x 2 – 5x p(3a) =

38 b. p(3a) p(x) = x 3 + 4x 2 – 5x p(3a) =

39 b. p(3a) p(x) = x 3 + 4x 2 – 5x p(3a) =

40 b. p(3a) p(x) = x 3 + 4x 2 – 5x p(3a) = (3a) 3

41 b. p(3a) p(x) = x 3 + 4x 2 – 5x p(3a) = (3a) 3

42 b. p(3a) p(x) = x 3 + 4x 2 – 5x p(3a) = (3a) 3 + 4(3a) 2

43 b. p(3a) p(x) = x 3 + 4x 2 – 5x p(3a) = (3a) 3 + 4(3a) 2

44 b. p(3a) p(x) = x 3 + 4x 2 – 5x p(3a) = (3a) 3 + 4(3a) 2 – 5(3a)

45 b. p(3a) p(x) = x 3 + 4x 2 – 5x p(3a) = (3a) 3 + 4(3a) 2 – 5(3a)

46 b. p(3a) p(x) = x 3 + 4x 2 – 5x p(3a) = (3a) 3 + 4(3a) 2 – 5(3a)

47 b. p(3a) p(x) = x 3 + 4x 2 – 5x p(3a) = (3a) 3 + 4(3a) 2 – 5(3a) = (3) 3 (a) 3

48 b. p(3a) p(x) = x 3 + 4x 2 – 5x p(3a) = (3a) 3 + 4(3a) 2 – 5(3a) = (3) 3 (a) 3 + 4

49 b. p(3a) p(x) = x 3 + 4x 2 – 5x p(3a) = (3a) 3 + 4(3a) 2 – 5(3a) = (3) 3 (a) 3 + 4(3) 2 (a) 2

50 b. p(3a) p(x) = x 3 + 4x 2 – 5x p(3a) = (3a) 3 + 4(3a) 2 – 5(3a) = (3) 3 (a) 3 + 4(3) 2 (a) 2 – 5(3a)

51 b. p(3a) p(x) = x 3 + 4x 2 – 5x p(3a) = (3a) 3 + 4(3a) 2 – 5(3a) = (3) 3 (a) 3 + 4(3) 2 (a) 2 – 5(3a)

52 b. p(3a) p(x) = x 3 + 4x 2 – 5x p(3a) = (3a) 3 + 4(3a) 2 – 5(3a) = (3) 3 (a) 3 + 4(3) 2 (a) 2 – 5(3a) = 27

53 b. p(3a) p(x) = x 3 + 4x 2 – 5x p(3a) = (3a) 3 + 4(3a) 2 – 5(3a) = (3) 3 (a) 3 + 4(3) 2 (a) 2 – 5(3a) = 27

54 b. p(3a) p(x) = x 3 + 4x 2 – 5x p(3a) = (3a) 3 + 4(3a) 2 – 5(3a) = (3) 3 (a) 3 + 4(3) 2 (a) 2 – 5(3a) = 27a 3

55 b. p(3a) p(x) = x 3 + 4x 2 – 5x p(3a) = (3a) 3 + 4(3a) 2 – 5(3a) = (3) 3 (a) 3 + 4(3) 2 (a) 2 – 5(3a) = 27a 3 + 4

56 b. p(3a) p(x) = x 3 + 4x 2 – 5x p(3a) = (3a) 3 + 4(3a) 2 – 5(3a) = (3) 3 (a) 3 + 4(3) 2 (a) 2 – 5(3a) = 27a 3 + 4(9)

57 b. p(3a) p(x) = x 3 + 4x 2 – 5x p(3a) = (3a) 3 + 4(3a) 2 – 5(3a) = (3) 3 (a) 3 + 4(3) 2 (a) 2 – 5(3a) = 27a 3 + 4(9)

58 b. p(3a) p(x) = x 3 + 4x 2 – 5x p(3a) = (3a) 3 + 4(3a) 2 – 5(3a) = (3) 3 (a) 3 + 4(3) 2 (a) 2 – 5(3a) = 27a 3 + 4(9)a 2

59 b. p(3a) p(x) = x 3 + 4x 2 – 5x p(3a) = (3a) 3 + 4(3a) 2 – 5(3a) = (3) 3 (a) 3 + 4(3) 2 (a) 2 – 5(3a) = 27a 3 + 4(9)a 2

60 b. p(3a) p(x) = x 3 + 4x 2 – 5x p(3a) = (3a) 3 + 4(3a) 2 – 5(3a) = (3) 3 (a) 3 + 4(3) 2 (a) 2 – 5(3a) = 27a 3 + 4(9)a 2 – 5(3a)

61 b. p(3a) p(x) = x 3 + 4x 2 – 5x p(3a) = (3a) 3 + 4(3a) 2 – 5(3a) = (3) 3 (a) 3 + 4(3) 2 (a) 2 – 5(3a) = 27a 3 + 4(9)a 2 – 15a = 27a 3 + 36a 2 – 15a

62 b. p(3a) p(x) = x 3 + 4x 2 – 5x p(3a) = (3a) 3 + 4(3a) 2 – 5(3a) = (3) 3 (a) 3 + 4(3) 2 (a) 2 – 5(3a) = 27a 3 + 4(9)a 2 – 15a = 27a 3 + 36a 2 – 15a c. 3p(a)

63 b. p(3a) p(x) = x 3 + 4x 2 – 5x p(3a) = (3a) 3 + 4(3a) 2 – 5(3a) = (3) 3 (a) 3 + 4(3) 2 (a) 2 – 5(3a) = 27a 3 + 4(9)a 2 – 15a = 27a 3 + 36a 2 – 15a c. 3p(a)

64 b. p(3a) p(x) = x 3 + 4x 2 – 5x p(3a) = (3a) 3 + 4(3a) 2 – 5(3a) = (3) 3 (a) 3 + 4(3) 2 (a) 2 – 5(3a) = 27a 3 + 4(9)a 2 – 15a = 27a 3 + 36a 2 – 15a c. 3p(a) p(x) = x 3 + 4x 2 – 5x

65 b. p(3a) p(x) = x 3 + 4x 2 – 5x p(3a) = (3a) 3 + 4(3a) 2 – 5(3a) = (3) 3 (a) 3 + 4(3) 2 (a) 2 – 5(3a) = 27a 3 + 4(9)a 2 – 15a = 27a 3 + 36a 2 – 15a c. 3p(a) p(x) = x 3 + 4x 2 – 5x 3[p(a)]

66 b. p(3a) p(x) = x 3 + 4x 2 – 5x p(3a) = (3a) 3 + 4(3a) 2 – 5(3a) = (3) 3 (a) 3 + 4(3) 2 (a) 2 – 5(3a) = 27a 3 + 4(9)a 2 – 15a = 27a 3 + 36a 2 – 15a c. 3p(a) p(x) = x 3 + 4x 2 – 5x 3[p(a)] 3[p(a)] =

67 b. p(3a) p(x) = x 3 + 4x 2 – 5x p(3a) = (3a) 3 + 4(3a) 2 – 5(3a) = (3) 3 (a) 3 + 4(3) 2 (a) 2 – 5(3a) = 27a 3 + 4(9)a 2 – 15a = 27a 3 + 36a 2 – 15a c. 3p(a) p(x) = x 3 + 4x 2 – 5x 3[p(a)] 3[p(a)] = 3

68 b. p(3a) p(x) = x 3 + 4x 2 – 5x p(3a) = (3a) 3 + 4(3a) 2 – 5(3a) = (3) 3 (a) 3 + 4(3) 2 (a) 2 – 5(3a) = 27a 3 + 4(9)a 2 – 15a = 27a 3 + 36a 2 – 15a c. 3p(a) p(x) = x 3 + 4x 2 – 5x 3[p(a)] 3[p(a)] = 3[

69 b. p(3a) p(x) = x 3 + 4x 2 – 5x p(3a) = (3a) 3 + 4(3a) 2 – 5(3a) = (3) 3 (a) 3 + 4(3) 2 (a) 2 – 5(3a) = 27a 3 + 4(9)a 2 – 15a = 27a 3 + 36a 2 – 15a c. 3p(a) p(x) = x 3 + 4x 2 – 5x 3[p(a)] 3[p(a)] = 3[

70 b. p(3a) p(x) = x 3 + 4x 2 – 5x p(3a) = (3a) 3 + 4(3a) 2 – 5(3a) = (3) 3 (a) 3 + 4(3) 2 (a) 2 – 5(3a) = 27a 3 + 4(9)a 2 – 15a = 27a 3 + 36a 2 – 15a c. 3p(a) p(x) = x 3 + 4x 2 – 5x 3[p(a)] 3[p(a)] = 3[

71 b. p(3a) p(x) = x 3 + 4x 2 – 5x p(3a) = (3a) 3 + 4(3a) 2 – 5(3a) = (3) 3 (a) 3 + 4(3) 2 (a) 2 – 5(3a) = 27a 3 + 4(9)a 2 – 15a = 27a 3 + 36a 2 – 15a c. 3p(a) p(x) = x 3 + 4x 2 – 5x 3[p(a)] 3[p(a)] = 3[

72 b. p(3a) p(x) = x 3 + 4x 2 – 5x p(3a) = (3a) 3 + 4(3a) 2 – 5(3a) = (3) 3 (a) 3 + 4(3) 2 (a) 2 – 5(3a) = 27a 3 + 4(9)a 2 – 15a = 27a 3 + 36a 2 – 15a c. 3p(a) p(x) = x 3 + 4x 2 – 5x 3[p(a)] 3[p(a)] = 3[a 3 + 4a 2 – 5a]

73 b. p(3a) p(x) = x 3 + 4x 2 – 5x p(3a) = (3a) 3 + 4(3a) 2 – 5(3a) = (3) 3 (a) 3 + 4(3) 2 (a) 2 – 5(3a) = 27a 3 + 4(9)a 2 – 15a = 27a 3 + 36a 2 – 15a c. 3p(a) p(x) = x 3 + 4x 2 – 5x 3[p(a)] 3[p(a)] = 3[a 3 + 4a 2 – 5a]

74 b. p(3a) p(x) = x 3 + 4x 2 – 5x p(3a) = (3a) 3 + 4(3a) 2 – 5(3a) = (3) 3 (a) 3 + 4(3) 2 (a) 2 – 5(3a) = 27a 3 + 4(9)a 2 – 15a = 27a 3 + 36a 2 – 15a c. 3p(a) p(x) = x 3 + 4x 2 – 5x 3[p(a)] 3[p(a)] = 3[a 3 + 4a 2 – 5a]

75 b. p(3a) p(x) = x 3 + 4x 2 – 5x p(3a) = (3a) 3 + 4(3a) 2 – 5(3a) = (3) 3 (a) 3 + 4(3) 2 (a) 2 – 5(3a) = 27a 3 + 4(9)a 2 – 15a = 27a 3 + 36a 2 – 15a c. 3p(a) p(x) = x 3 + 4x 2 – 5x 3[p(a)] 3[p(a)] = 3[a 3 + 4a 2 – 5a] = 3(a 3 )

76 b. p(3a) p(x) = x 3 + 4x 2 – 5x p(3a) = (3a) 3 + 4(3a) 2 – 5(3a) = (3) 3 (a) 3 + 4(3) 2 (a) 2 – 5(3a) = 27a 3 + 4(9)a 2 – 15a = 27a 3 + 36a 2 – 15a c. 3p(a) p(x) = x 3 + 4x 2 – 5x 3[p(a)] 3[p(a)] = 3[a 3 + 4a 2 – 5a] = 3(a 3 )

77 b. p(3a) p(x) = x 3 + 4x 2 – 5x p(3a) = (3a) 3 + 4(3a) 2 – 5(3a) = (3) 3 (a) 3 + 4(3) 2 (a) 2 – 5(3a) = 27a 3 + 4(9)a 2 – 15a = 27a 3 + 36a 2 – 15a c. 3p(a) p(x) = x 3 + 4x 2 – 5x 3[p(a)] 3[p(a)] = 3[a 3 + 4a 2 – 5a] = 3(a 3 ) + 3(4a 2 )

78 b. p(3a) p(x) = x 3 + 4x 2 – 5x p(3a) = (3a) 3 + 4(3a) 2 – 5(3a) = (3) 3 (a) 3 + 4(3) 2 (a) 2 – 5(3a) = 27a 3 + 4(9)a 2 – 15a = 27a 3 + 36a 2 – 15a c. 3p(a) p(x) = x 3 + 4x 2 – 5x 3[p(a)] 3[p(a)] = 3[a 3 + 4a 2 – 5a] = 3(a 3 ) + 3(4a 2 )

79 b. p(3a) p(x) = x 3 + 4x 2 – 5x p(3a) = (3a) 3 + 4(3a) 2 – 5(3a) = (3) 3 (a) 3 + 4(3) 2 (a) 2 – 5(3a) = 27a 3 + 4(9)a 2 – 15a = 27a 3 + 36a 2 – 15a c. 3p(a) p(x) = x 3 + 4x 2 – 5x 3[p(a)] 3[p(a)] = 3[a 3 + 4a 2 – 5a] = 3(a 3 ) + 3(4a 2 ) – 3(5a)

80 b. p(3a) p(x) = x 3 + 4x 2 – 5x p(3a) = (3a) 3 + 4(3a) 2 – 5(3a) = (3) 3 (a) 3 + 4(3) 2 (a) 2 – 5(3a) = 27a 3 + 4(9)a 2 – 15a = 27a 3 + 36a 2 – 15a c. 3p(a) p(x) = x 3 + 4x 2 – 5x 3[p(a)] 3[p(a)] = 3[a 3 + 4a 2 – 5a] = 3(a 3 ) + 3(4a 2 ) – 3(5a) = 3a 3 + 12a 2 – 15a

81 Ex. 3 For each graph: 1.Describe the end behavior 2.Determine if the degree is even or odd. 3.State the number of real zeros. y (solutions) a. x

82 Ex. 3 For each graph: 1.Describe the end behavior 2.Determine if the degree is even or odd. 3.State the number of real zeros. y (solutions) a. x

83 Ex. 3 For each graph: 1.Describe the end behavior 2.Determine if the degree is even or odd. 3.State the number of real zeros. y (solutions) a. x 1. As x +∞

84 Ex. 3 For each graph: 1.Describe the end behavior 2.Determine if the degree is even or odd. 3.State the number of real zeros. y (solutions) a. x 1. As x +∞

85 Ex. 3 For each graph: 1.Describe the end behavior 2.Determine if the degree is even or odd. 3.State the number of real zeros. y (solutions) a. x 1. As x +∞, f(x)

86 Ex. 3 For each graph: 1.Describe the end behavior 2.Determine if the degree is even or odd. 3.State the number of real zeros. y (solutions) a. x 1. As x +∞, f(x)

87 Ex. 3 For each graph: 1.Describe the end behavior 2.Determine if the degree is even or odd. 3.State the number of real zeros. y (solutions) a. x 1. As x +∞, f(x)

88 Ex. 3 For each graph: 1.Describe the end behavior 2.Determine if the degree is even or odd. 3.State the number of real zeros. y (solutions) a. x 1. As x +∞, f(x) –∞

89 Ex. 3 For each graph: 1.Describe the end behavior 2.Determine if the degree is even or odd. 3.State the number of real zeros. y (solutions) a. x 1. As x +∞, f(x) –∞ As x –∞

90 Ex. 3 For each graph: 1.Describe the end behavior 2.Determine if the degree is even or odd. 3.State the number of real zeros. y (solutions) a. x 1. As x +∞, f(x) –∞ As x –∞

91 Ex. 3 For each graph: 1.Describe the end behavior 2.Determine if the degree is even or odd. 3.State the number of real zeros. y (solutions) a. x 1. As x +∞, f(x) –∞ As x –∞, f(x)

92 Ex. 3 For each graph: 1.Describe the end behavior 2.Determine if the degree is even or odd. 3.State the number of real zeros. y (solutions) a. x 1. As x +∞, f(x) –∞ As x –∞, f(x)

93 Ex. 3 For each graph: 1.Describe the end behavior 2.Determine if the degree is even or odd. 3.State the number of real zeros. y (solutions) a. x 1. As x +∞, f(x) –∞ As x –∞, f(x)

94 Ex. 3 For each graph: 1.Describe the end behavior 2.Determine if the degree is even or odd. 3.State the number of real zeros. y (solutions) a. x 1. As x +∞, f(x) –∞ As x –∞, f(x) –∞

95 Ex. 3 For each graph: 1.Describe the end behavior 2.Determine if the degree is even or odd. 3.State the number of real zeros. y (solutions) a. x 1. As x +∞, f(x) –∞ As x –∞, f(x) –∞

96 Ex. 3 For each graph: 1.Describe the end behavior 2.Determine if the degree is even or odd. 3.State the number of real zeros. y (solutions) a. x 1. As x +∞, f(x) –∞ As x –∞, f(x) –∞

97 Ex. 3 For each graph: 1.Describe the end behavior 2.Determine if the degree is even or odd. 3.State the number of real zeros. y (solutions) a. x 1. As x +∞, f(x) –∞ As x –∞, f(x) –∞ 2. Even degree

98 Ex. 3 For each graph: 1.Describe the end behavior 2.Determine if the degree is even or odd. 3.State the number of real zeros. y (solutions) a. x 1. As x +∞, f(x) –∞ As x –∞, f(x) –∞ 2. Even degree

99 Ex. 3 For each graph: 1.Describe the end behavior 2.Determine if the degree is even or odd. 3.State the number of real zeros. y (solutions) a. x 1. As x +∞, f(x) –∞ As x –∞, f(x) –∞ 2. Even degree 3. 2 real zeros

100 Ex. 4 For each graph: 1.Describe the end behavior 2.Determine if the degree is even or odd. 3.State the number of real zeros. y (solutions) a. x 1. As x +∞, f(x) As x –∞, f(x) 2. degree 3. real zero(s)

101 Ex. 4 For each graph: 1.Describe the end behavior 2.Determine if the degree is even or odd. 3.State the number of real zeros. y (solutions) a. x 1. As x +∞, f(x) +∞ As x –∞, f(x) –∞ 2. Odd degree 3. 1 real zero


Download ppt "6.3 – Evaluating Polynomials. degree (of a monomial) 5x 2 y 3 degree ="

Similar presentations


Ads by Google